Life Events and Personality Trait Change. Issue 1 (3rd December 2016) - Bleidorn, Wiebke; Hopwood, Christopher J.; Lucas, Richard E.
Abstract: Objective: Theory and research have emphasized the impact of life events on personality trait change. In this article, we review prospective research on personality trait change in response to nine major life events in the broader domains of love and work. Method: We expected to find that life events lead to personality trait change to the extent that they have a lasting influence on individuals' thoughts, feelings, and behavior. Moreover, we predicted that love‐related life events such as marriage or parenthood would be more strongly related to changes in traits that emphasize affective content, whereas work‐related life events would be more likely to lead to change in traits that reflect behavioral or cognitive content. Results: The current state of research provided some evidence that life events can lead to changes in personality traits and that different life events may be differently related to specific trait domains. Conclusions: A more general conclusion emerging from this review is that the evidence for the nature, shape, and timing of personality trait change in response to life events is still preliminary. We discuss the implications of the results for theory and research and provide directions for future studies on life events and personality trait change.